Analisis Perbandingan Model Problem Based Learning (PBL) berbasis Edmodo dan Google Classroom untuk Meningkatkan Hasil Belajar dan Interaksi Guru dan Siswa pada Pembelajaran Komputer dan Jaringan Dasar Kelas X pada Jurusan Teknik Komputer dan Informasi (S: (Studi Kasus: SMKN 5 Malang) - Raka Wisnu Wijaya; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The development of information technology, which is supported by the presence of the Internet, has had a positive impact on education and made the online and offline learning process easier. However, there are problems with students of SMKN 5 Malang in carrying out the learning that is given by lectures by teachers of the department of computer technology and information at SMKN 5. In this study, teachers should be encouraged to use learning media from Edmodo and Google Classroom with a population of 10 people. All students in class X, Faculty of Computer Technology and The information totaled 67, namely X TKI-3 and X TKI-5 media Edmodo and Google shows and questionnaire in the form of questions interaction of teachers and students during treatment. In this study, data acquisition techniques in the form of interviews with teachers from subjects at SMKN 5 Malang are used. This study compares media Edmodo and Google actions with model learning problem-based learning. This type of quasi-experimental study using the non-equivalent control group design was used in this study. Based on hypothesis tests, the researchers receive the results that there is a difference between Edmodo and Google Classroom with the learning model of learning problem-based learning, namely that the learning outcomes of TKI-5 students in class X who use Edmodo are higher than that of men -Whitney test test package.